The mystery of Antarctic climate change and its relation to geomagnetic field - Kilifarska, N. A.; Bakhmutov, V. G.; Melnyk, G. V. (Ukrainian Antarctic Journal, 2013)
The regional characteristics of changing climate are serious challenge for the current understanding regarding the driving factors of climate variability. Here we present a plausible explanation for the diversity of regional response of Antarctic climate to uniform enhancement of greenhouse gases, i.e. the simultaneous warming of the Western and cooling of the Eastern Antarctica. The explanation is related to the heterogeneously distributed geomagnetic field, controlling the intensity and depth of particles penetration in the Earth’s atmosphere. We discover that at seasonal basis the solar proton activity initiates enhancement of the ozone density in the lower stratosphere over East Antarctica. This starts up the mechanism for drying of the upper troposphere and lower stratosphere − through O3 influence on temperature and static stability of air masses. Thus warming of the tropopause region reduces static stability, blocking upward propagation of the water vapour from the wetter middle troposphere. As a result the Earth’s longwave radiation freely escapes in the space − a process accompanied with persistent cooling of the surface air in the eastern part of the continent. During the passed half a century the ozone density in the Western Antarctica is substantially lower, that diminished severely the ozone-water vapour cooling effect.